PENGARUH TERAPI NEBULIZER TERHADAP FREKUENSI NAPAS PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) - Ratna Dewi; Sarmaida Siregar; Mukhtar Effendi Harahap; Christine Handayani Siburian (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Physiological changes due to inflammation in COPD patients significantly reduce the low level of carbon dioxide in the blood which causes shortness of breath with increased respiratory rate, so the importance of therapy that quickly dilutes secretions, clears the airway, and weakens the respiratory tract such as nebulizer therapy. This study aims to identify the effect of nebulizer therapy on respiratory rate in COPD patients. The research design used was a quasi-experimental pre and post test one sample test. The sample in this study amounted to 49 respondents by calculating the respiratory rate through the inspection method. The test used was the Wilcoxon signed rank test. The results of this study showed that there was an effect before and after nebulizer therapy on respiratory rate in COPD patients with value = 0.000. Based on the research, it can be concluded that the action of nebulizer therapy greatly affects the decrease in respiratory rate in COPD patients. It is recommended that nurses perform nebulizer therapy with the right frequency and duration for the successful effect of decreasing respiratory frequency.